GREEN GAS EMISSIONS AND CORPORATE GOVERNANCE: FINANCIAL INDUSTRY IN INDONESIA AND MALAYSIA - Risty, Ilyona (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The accelerating threat of climate change increases the importance of corporate commitment to the climate transition, including the important role of the financial industry in aligning with net zero emissions goals. The International Sustainability Standards Board has issued the latest standards in 2023 related to general requirements and a climate that encourages every organization to report a sustainability report. This research was conducted to determine the relationship between organizational governance and the emissions produced (green gas emissions) which will indirectly affect climate change. This research took samples from the financial industry and public companies contained in the S&P database. This research uses a quantitative approach to find out the relationship of organizational governance and emissions. The research will provide benefits to the literature related to the role of governance in the management of emissions produced by organization.